PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP PRESTASI KERJA DI DINAS PENDAPATAN DAERAH KOTA PALEMBANG - Hakim, Marwan (Universitas muhammadiyah palembang, 2017)
Design / Methodology / Approach: the data used for analysis in this study isqualitative data , the variables in this study are motivation , workenvironment , work culture and performance achievement . The population inthis study is the Regional Revenue Service Employees Palembang ,amounting to 256 employees . The sampling technique used in this study issimple random sampling . The sample in this study using the formulaobtained slovin to 156 people . The method of analysis in this study usingOLS regression ( Ordinary Least Square ) Findings : Overall variablemotivation , work environment and work culture have a significant effect onthe performance of the Regional Revenue Service employee Palembang .But individually , motivation significant effect on work performance , workenvironment variables have a significant effect on work performance andwork culture variables significantly influence the achievement of RegionalRevenue Office of Palembang .